2020
DOI: 10.4236/ojem.2020.83007
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Waiting Times and Determinants of Prolonged Length of Stay in a Botswana Referral Hospital

Abstract: Introduction: Emergency medicine is a critical component of quality public health service. In fact length of stay and waiting times in the Emergency department are key indicators of quality. The aim of this study was to determine waiting times and determinants of prolonged length of stay (LOS) in the Princess Marina Hospital Emergency Department. Methods: This was a retrospective observational study. It was done at Princess Marina, a referral hospital in Gaborone, Botswana. Triage forms of patients who present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 23 publications
(27 reference statements)
0
14
1
Order By: Relevance
“…The increased length of stay in the EC is primarily due to other factors such as the laboratory results and radiological imaging turnaround times [27] . Similarly, in a Botswana tertiary hospital, organizational variables such as multiple referrals and investigations were the leading causes of a lengthy stay in the EC [15] .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The increased length of stay in the EC is primarily due to other factors such as the laboratory results and radiological imaging turnaround times [27] . Similarly, in a Botswana tertiary hospital, organizational variables such as multiple referrals and investigations were the leading causes of a lengthy stay in the EC [15] .…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, because the Botswana referral system follows a hierarchical order in which patients travel through the district hospital before reaching the tertiary hospital, some patients are further transferred to a tertiary hospital, adding to the delay in patient management. A study in Botswana showed that 14.6% of trauma patients died after arriving at the secondary hospital [15] . The findings underscore the necessity for direct transfers to higher-level facilities without following a hierarchical referral system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sub-Saharan African countries recognised that prolonged LOS has become a daily reality affecting the functionality of the EDs and reached consensus that further investigations was vital to try and reduce prolonged LOS in the ED [ 22 , 23 ]. The study conducted in Botswana found that ED waiting times and length of stay were prolonged [ 24 ]. Although it was indicated in the study conducted in Nigeria that the ideal ED LOS was 6 h, findings from the study conducted in a teaching hospital ED showed patient ED stay of over 24 h [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies into waiting time in healthcare institutions, focusing mainly on outpatients [ 14 , 15 ] and Emergency Departments [ 16 , 17 ]. The research has mostly been carried out from the perspective of the country, the region, or the entire hospital [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%